2020
DOI: 10.1186/s13018-020-02037-2
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and radiographic characteristics of avascular necrosis after pediatric femoral neck fracture: a systematic review and retrospective study of 115 patients

Abstract: Background Avascular necrosis (AVN) after pediatric femoral neck fracture (PFNF) showed poor prognosis, but its clinical and radiographic characteristics remained unclear. Methods A systematic review and a retrospective study were performed to evaluate the clinical and radiographic characteristics of patients with AVN after PFNF. Results A total of 686 patients with PFNF and 203 patients with AVN from 21 articles were analyzed. Ratliff’s classification was used in 178 patients, with types I, II, and III AV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Moreover, due to the rapid development of social economy, high-energy injuries caused by car accidents and falls from height are increasing, and the incidence of femoral neck fractures in young and middle-aged people is increasing year by year [ 4 ]. Young and middle-aged patients require joint function activities, so it is necessary to maintain the shape and function of the original joint through reduction as much as possible [ 5 , 6 ]. One study showed that the incidence of postoperative femoral head necrosis was 16% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to the rapid development of social economy, high-energy injuries caused by car accidents and falls from height are increasing, and the incidence of femoral neck fractures in young and middle-aged people is increasing year by year [ 4 ]. Young and middle-aged patients require joint function activities, so it is necessary to maintain the shape and function of the original joint through reduction as much as possible [ 5 , 6 ]. One study showed that the incidence of postoperative femoral head necrosis was 16% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that the collapse rate of the lesion that exceeds 2/3 of the inner side of the weight bearing part is high. When the lesion extends laterally to the edge of the acetabulum, the femoral head collapse is more common [29][30][31] . The experimental group implanted BCP material in a prominent imaging position, with a basically intact structure and a columnar shape; Overall observation showed no collapse in the necrotic area of the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…The necrotic lesion mostly occurs at the superior, medial, and anterior areas of the ischemic femoral head 32 . According to the Japanese Investigation Committee (JIC) classification system (Table 2 ), several studies had indicated that the lesion exceeding the medial 2/3 of the weight‐bearing portion had a higher collapse rate and a faster progression of stage, and femoral head collapse occurred more often when the lesion extended laterally to the acetabular edge 47 , 48 , 49 , 50 , 51 (Table 3 ). One explanation was that the changes of bone structure in weight‐bearing portion reduced the stress transfer efficiency of principal compressive trabeculae after osteonecrosis and caused severe damage to the load‐bearing capacity.…”
Section: Structural Deterioration In Necrotic Femoral Headmentioning
confidence: 99%